2008
DOI: 10.1038/ncb1700
|View full text |Cite
|
Sign up to set email alerts
|

Sirt1 contributes critically to the redox-dependent fate of neural progenitors

Abstract: Repair processes that are activated in response to neuronal injury, be it inflammatory, ischaemic, metabolic, traumatic or other cause, are characterized by a failure to replenish neurons and by astrogliosis. The underlying molecular pathways, however, are poorly understood. Here, we show that subtle alterations of the redox state, found in different brain pathologies, regulate the fate of mouse neural progenitor cells (NPCs) through the histone deacetylase (HDAC) Sirt1. Mild oxidation or direct activation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
359
3
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 423 publications
(388 citation statements)
references
References 42 publications
22
359
3
4
Order By: Relevance
“…Recently, Prozorovski et al (30) showed that oxidative conditions repressed Mash1 expression in neonates and cultured NPCs from E17.5 embryos and indicated that the repression of Mash1 was mediated by the complex of Hes1 and SIRT1. They suggested that SIRT1 participated in oxidation-mediated suppression of neurogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Prozorovski et al (30) showed that oxidative conditions repressed Mash1 expression in neonates and cultured NPCs from E17.5 embryos and indicated that the repression of Mash1 was mediated by the complex of Hes1 and SIRT1. They suggested that SIRT1 participated in oxidation-mediated suppression of neurogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1 was shown to regulate the promoter of the MashI gene in somatic stem cell neural differentiation in mice (5). To identify the downstream effects of SIRT1 down-regulation in hESC differentiation, we performed chromatin IP (ChIP) experiments in Shef-1 hESC by using an anti-SIRT1 antibody and by hybridizing the immunoprecipitated DNA fragments on an Agilent human promoter ChIP-on-chip microarray containing 474,392 probes, which cover almost all described human promoters and many known regulatory regions.…”
Section: Sirt1 Epigenetically Regulates Developmental Genes During Plmentioning
confidence: 99%
“…Defects in HSC self-renewal under both basal and low oxygen conditions are exacerbated in older mice compared with young adults (Ou et al, 2010). The role of SIRT1 in adult NSCs has not yet been characterized, but SIRT1 plays a role in directing cell fate decisions of embryonic neural progenitors in response to different extracellular conditions (Hisahara et al, 2008;Prozorovski et al, 2008). In the presence of low amounts of growth factors, SIRT1 promotes neuronal differentiation in cultures of murine neural progenitors, and acute deletion of Sirt1 at embryonic stages results in fewer neurons in vivo (Hisahara et al, 2008).…”
Section: Histone Acetylation In Aging Stem Cellsmentioning
confidence: 99%
“…In the presence of low amounts of growth factors, SIRT1 promotes neuronal differentiation in cultures of murine neural progenitors, and acute deletion of Sirt1 at embryonic stages results in fewer neurons in vivo (Hisahara et al, 2008). However, under conditions of mild oxidative stress, SIRT1 contributes to decreased production of neurons and increased astrocytes, an effect linked to SIRT1's effects on H3K9ac levels of proneural gene Mash1/Ascl1 (Prozorovski et al, 2008). In the context of increased oxidative stress in the brain during aging or disease (Monje et al, 2003), misregulation of SIRT1 may contribute to the decrease in neurogenesis with age.…”
Section: Histone Acetylation In Aging Stem Cellsmentioning
confidence: 99%